Generation Z Work Motivation in Indonesia - Diah Putri Lestari; Mirwan Surya Perdhana (PT. Publikasiku Academic Solution, 2023)
This study aims to identify the most important work motivation factors for Generation Z that can serve as a solid basis for practical decision-making to determine strategies for employers in attracting and retaining Generation Z employees who will dominate the workforce in Indonesia in the future. A mixed methods approach was used in this study. Quantitative instruments are used for MWMS (Multidimensional Work Motivation Scale) while interviews are used for qualitative instruments. This study involved 293 employees as questionnaire respondents and 5 employees as resource persons. At the quantitative stage, introjection rules are prominent in controlled motivation, and in autonomous motivation, there is an emphasis on identified rules. At the qualitative stage, of the six MWMS factors, four appear more often in the analysis Content of the interview: The need for autonomy, competence, relationships, and compensation. Relationships are the most prevalent, four of the six factors. In addition, it was found that flexibility is another motivational factor that is also important for Generation Z employees who have access to able to work remotely. Research limitations/implications – It's important to offer motivators that are valued by Generation Z in order to attract the best candidates. Organizations must not only create an inclusive and understanding work environment but also be able to communicate strong branding in order to attract the best talent of Generation Z. This is the first study of its kind to examine work motivation specifically in Generation Z through a mixed method approach with Multidimensional Work Motivation Scale (MWMS) measurements in the Asian context of Indonesia.